Increasing Tourist Visits through the Development Model of Tourism Village based on Local Culture - REVIDA, Erika; MUNTHE, Hadriana Marhaeni; PURBA, Sukarman (Journal of Environmental Management and Tourism; Vol 13 No 4 (2022): JEMT, Volume XIII, Issue 4(60), Summer 2022DO - 10.14505/jemt.v13.4(60).21, 2022)
The general objective of this research paper is to analyze the model of developing a tourism village based on local culture in order to increase the number of tourist visits. The specific purpose of our study was to analyze: the effect of the attraction development model, the effect of the accommodation development model, the influence of the amenity’s development model, and find a tourist village development model, all these with the scope to increase the tourist visits. The sample used in this research is formed from tourists and the people from the tourist village of Dokan Karo, North Sumatera. The data analysis technique used, was multiple regression analysis. The results released a positive influence between the attraction development model for tourist arrivals, the accommodation development model effect, and the amenity development model effect upon tourist visits. The model for developing a tourism village based on local culture in increasing tourist visits to Dokan Karo, North Sumatera, are the attractions, accommodations, amenities, accessibility, and the local culture-based hospitality.